Nup96 and HOS1 Are Mutually Stabilized and Gate CONSTANS Protein Level, Conferring Long-Day Photoperiodic Flowering Regulation in Arabidopsis - Cheng, Zhiyuan; Zhang, Xiaomei; Huang, Penghui; Huang, Guowen; Zhu, Jinglong; Chen, Fulu; Miao, Yuchen; Liu, Liangyu; Fu, Yong-Fu; Wang, Xu (The Plant cell, 2020)
The nuclear pore complex profoundly affects the timing of flowering; however, the underlying mechanisms are poorly understood. Here, we report that ( ) acts as a negative regulator of long-day photoperiodic flowering in Arabidopsis ( ). Through multiple approaches, we identified the E3 ubiquitin ligase HIGH EXPRESSION OF OSMOTICALLY RESPONSIVE GENE1 (HOS1) and demonstrated its interaction in vivo with Nup96. Nup96 and HOS1 mainly localize and interact on the nuclear membrane. Loss of function of leads to destruction of HOS1 proteins without a change in their mRNA abundance, which results in overaccumulation of the key activator of long-day photoperiodic flowering, CONSTANS (CO) proteins, as previously reported in mutants. Unexpectedly, mutation of strikingly diminishes Nup96 protein level, suggesting that Nup96 and HOS1 are mutually stabilized and thus form a novel repressive module that regulates CO protein turnover. Therefore, the and single and double mutants have highly similar early-flowering phenotypes and overlapping transcriptome changes. Together, this study reveals a repression mechanism in which the Nup96-HOS1 repressive module gates the level of CO proteins and thereby prevents precocious flowering in long-day conditions.